2015
DOI: 10.1089/fpd.2014.1934
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of ColV Plasmid-Linked Genes andIn VivoPathogenicity of Avian Strains ofEscherichia coli

Abstract: Avian pathogenic Escherichia coli (APEC) causes extraintestinal infections in birds, leading to an increase in the cost of poultry production. The ColV plasmid-linked genes iroN, ompT, hlyF, iss, and iutA have previously been suggested to be predictors of the virulence of APEC. In this research, we analyzed the frequencies of these genes in a Brazilian collection of E. coli isolated from birds with colibacillosis (APEC) and from apparently healthy birds (avian fecal [A(fecal)]), as well as from the litter of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 28 publications
3
25
0
6
Order By: Relevance
“…We found one bacterium, from bovine meat meal, accumulating four genes associated with APEC and one gene associated with atypical EPEC. Even with the presence of four out of five APEC virulence predictor genes, we cannot state that it is a pathogenic bacterium (Oliveira et al, 2015). To confirm this information, it would be necessary to inoculate it in one-day-old chicks and evaluate the development of an infection.…”
Section: Resultsmentioning
confidence: 98%
“…We found one bacterium, from bovine meat meal, accumulating four genes associated with APEC and one gene associated with atypical EPEC. Even with the presence of four out of five APEC virulence predictor genes, we cannot state that it is a pathogenic bacterium (Oliveira et al, 2015). To confirm this information, it would be necessary to inoculate it in one-day-old chicks and evaluate the development of an infection.…”
Section: Resultsmentioning
confidence: 98%
“…The results showed that highly pathogenic APEC strains harboured an average number of 4.6 VGs while an average of 4.3 and 3.9 were found among medium and low pathogenic APEC strains, respectively. The average number of VGs in AFEC isolates was 1.3. Subsequently, studies have used the pentaplex-PCR described by Johnson et al (2008b) and confirmed that it is a rapid diagnostic tool to differentiate between APEC and AFEC (de Oliveira et al, 2015;Dissanayake et al, 2014;Hussein et al, 2013). Despite the geographical variations of the studies, Kobayashi et al (2011) (68% -72%), Hussein et al (2013) (90% -94%) and de Oliverira et al (2015) (82% -95%) reported similar frequencies of the five VGs as Johnson et.al.…”
Section: Few In Vivomentioning
confidence: 86%
“…Johnson et al (2008b) used a large sample size, combined with extensive genotyping to select VG markers for APEC. Despite the variation in frequency of these five VGs in different overseas studies, a significant association between them and APEC has been reported (de Oliveira et al, 2015;Dissanayake et al, 2014;Hussein et al, 2013).…”
Section: Few In Vivomentioning
confidence: 91%
See 1 more Smart Citation
“…Although all these detected genes showed important virulence characteristics attributed to the APEC pathotype (Lynne et al 2006, Chouikha et al 2008, Johnson et al 2008, none of the E. coli strains could be characterized as belonging to this pathotype, because they did not have all the necessary genes. However, it is important to emphasize that, according to Oliveira et al (2015), pathogenic strains usually have two or more predictive genes for the APEC pathotype, whereas isolates with fewer than two genes are rarely pathogenic. In contrast, Johnson et al (2008) state the need for at least four types of predictor genes to differentiate strains with pathogenic potential from commensal E. coli.…”
Section: Discussionmentioning
confidence: 99%